Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1073/pnas.2203769119
|View full text |Cite|
|
Sign up to set email alerts
|

In situ architecture of the lipid transport protein VPS13C at ER–lysosome membrane contacts

Abstract: VPS13 is a eukaryotic lipid transport protein localized at membrane contact sites. Previous studies suggested that it may transfer lipids between adjacent bilayers by a bridge-like mechanism. Direct evidence for this hypothesis from a full-length structure and from electron microscopy (EM) studies in situ is still missing, however. Here, we have capitalized on AlphaFold predictions to complement the structural information already available about VPS13 and to generate a full-length model of human VPS13C, the Pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 58 publications
4
37
0
Order By: Relevance
“…In their recent paper, Cai et al produced a more tightly wound model which spanned 29.3 nm and left both ends of the protein free of membrane. However, their measurements in cells expressing full-length VPS13C showed the distribution of distances between ER and lysosome spanned by VPS13C centred around 32.5 nm (Cai et al, 2022), the exact length of VPS13C in our models ( Video 1 ). Intriguingly, the density mapping of Cai et al (2022) showed that there was a substantial density on the C-terminal lysosomal side of the contact and little density where the protein was in contact via the chorein domain with the ER, suggesting a more stable conformation of the C terminus in their association with membranes than the N terminus.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…In their recent paper, Cai et al produced a more tightly wound model which spanned 29.3 nm and left both ends of the protein free of membrane. However, their measurements in cells expressing full-length VPS13C showed the distribution of distances between ER and lysosome spanned by VPS13C centred around 32.5 nm (Cai et al, 2022), the exact length of VPS13C in our models ( Video 1 ). Intriguingly, the density mapping of Cai et al (2022) showed that there was a substantial density on the C-terminal lysosomal side of the contact and little density where the protein was in contact via the chorein domain with the ER, suggesting a more stable conformation of the C terminus in their association with membranes than the N terminus.…”
Section: Discussionmentioning
confidence: 73%
“…The ER is relatively enriched in those lipid species compared to endo-lysosomes (Escribá et al, 2015;Guo et al, 2009;Horvath and Daum, 2013;Pogozheva et al, 2022;Reglinski et al, 2020;Tauchi-Sato et al, 2002;van Meer and de Kroon, 2011;van Meer et al, 2008). Despite this, the levels of phosphatidylcholine, phosphatidylserine, phosphatidylinositol, and sphingomyelin increase in the lysosome in VPS13C knockout clones (Hancock-Cerutti et al, 2022). Intriguingly, this suggests that VPS13C-mediated lipid transfer can be compensated for by other mechanisms.…”
Section: Ideas and Speculationsmentioning
confidence: 99%
See 3 more Smart Citations